2015
DOI: 10.1111/imr.12373
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of Mac‐1 in autoimmune disease

Abstract: Mac-1 (CD11b/CD18) is a β2 integrin classically regarded as a pro-inflammatory molecule because of its ability to promote phagocyte cytotoxic functions and enhance the function of several effector molecules such as FcγR, uPAR, and CD14. Nevertheless, recent reports have revealed that Mac-1 also plays significant immunoregulatory roles, and genetic variants in ITGAM, the gene that encodes CD11b, confer risk for the autoimmune disease systemic lupus erythematosus (SLE). This has renewed interest in the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
87
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 159 publications
0
87
2
5
Order By: Relevance
“…14, 17-21, and reviewed in ref. 22), including increased tissue infiltration of leukocytes and immune-mediated injury in lupus-prone mice (19,20). These data further suggest that CD11b plays a protective role in SLE.…”
mentioning
confidence: 59%
“…14, 17-21, and reviewed in ref. 22), including increased tissue infiltration of leukocytes and immune-mediated injury in lupus-prone mice (19,20). These data further suggest that CD11b plays a protective role in SLE.…”
mentioning
confidence: 59%
“…CD18 integrins are composed of a unique CD11 subunit noncovalently bound to CD18 (β 2 integrin, Hsa21). The role of these integrins is to support key leukocyte adhesive functions critical to antigen presentation, efferocytosis and pathogen clearance [187]. Some reports suggest that CD18 is overexpressed on Down syndrome myeloid cells [188].…”
Section: Genetic Influence Of Trisomy 21 On Immune System Disturbancementioning
confidence: 99%
“…However, other studies have not detected any increased CD18 on myeloid cells [189], and the differential findings may be related to whether the cells used had been transformed (lymphoblastoid cells). Due to the importance of CD18 in mediating appropriate leukocyte responses [187], the potential correlation of CD18 expression to gene dosage in Down syndrome should be examined carefully.…”
Section: Genetic Influence Of Trisomy 21 On Immune System Disturbancementioning
confidence: 99%
“…ID4 regulates cell differentiation in multiple cell types and also enhances estrogen production and signaling (78); how this influences the course of LN is currently unknown. ITGAM encodes for the alpha chain of the CD11b (complement receptor 3) adhesion molecule that is expressed on myeloid cells and has both protective and pro-inflammatory functions in inflammation (79, 80). ITGAM polymorphisms are associated both with lupus susceptibility and severity and recent functional studies have determined that the dominant polymorphism R77H decreases ligand binding to CD11b under flow conditions and may compromise the inhibitory functions of the molecule by altering the affinity of the molecule for its ligands (79, 80).…”
Section: Linking Genotype To Phenotypementioning
confidence: 99%
“…ITGAM encodes for the alpha chain of the CD11b (complement receptor 3) adhesion molecule that is expressed on myeloid cells and has both protective and pro-inflammatory functions in inflammation (79, 80). ITGAM polymorphisms are associated both with lupus susceptibility and severity and recent functional studies have determined that the dominant polymorphism R77H decreases ligand binding to CD11b under flow conditions and may compromise the inhibitory functions of the molecule by altering the affinity of the molecule for its ligands (79, 80). We found that the increase in expression of CD11b in all three murine models is due both to an increase in CD11b expressing cell infiltrates and an increase in CD11b expression on renal macrophages.…”
Section: Linking Genotype To Phenotypementioning
confidence: 99%